Moving from EDID Words to Policy Action: A Case Study of a Teacher Education Program’s Admissions Policy Reform - MacMath, Sheryl; Salingré, Barbara; Sivia, Awneet (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
Regardless of the commitments that universities and teacher education programs (TEPs) have publicly stated regarding equity, diversity, inclusion, or decolonization (EDID), rarely do these commitments impact their admission policies or practices. Through examining a small program’s efforts at implementing EDID change over a three-year period, this article provides critical reflections, questions, and action steps for TEPs looking to move beyond talking about the importance of EDID, to actually altering policies and procedures to address systemic change. Utilizing the concepts of “equity in” and “equity through” admissions, intake variables (Multiple Mini Interview [MMI], Program Preparation, GPA) were analyzed quantitatively and used in this beginning participatory action research project. Results illustrate the benefits of the MMI, the need for program admissions to account for capacities in relation to anti-racism directly, rather than just generally referring to equity, and the need for admission practices to reflect an appreciation of the complexities around identity and ethics.